Evaluating the impact of visualization of risk upon emergency route-planning. Issue 5 (3rd May 2020) - Cheong, Lisa; Kinkeldey, Christoph; Burfurd, Ingrid; Bleisch, Susanne; Duckham, Matt
ABSTRACT: This paper reports on a controlled experiment evaluating how different cartographic representations of risk affect participants' performance on a complex spatial decision task: route planning. The specific experimental scenario used is oriented towards emergency route-planning during flood response. The experiment compared six common abstract and metaphorical graphical symbolizations of risk. The results indicate a pattern of less-preferred graphical symbolizations associated with slower responses and lower-risk route choices. One mechanism that might explain these observed relationships would be that more complex and effortful maps promote closer attention paid by participants and lower levels of risk taking. Such user considerations have important implications for the design of maps and mapping interfaces for emergency planning and response. The data also highlights the importance of the 'right decision, wrong outcome problem' inherent in decision-making under uncertainty: in individual instances, more risky decisions do not always lead to worse outcomes.